Guidelines on the role of skin care in the management of mobile populations. (24th January 2013) - Fuller, Lucinda Claire; Hay, Roderick; Morrone, Aldo; Naafs, Ben; Ryan, Terence J.; Sethi, Aisha
Abstract The Task Force for Skin Care for All: Community Dermatology, when seeking to collate evidence for capacity to benefit, wanted to know how best to manage mobile populations. The task force met where there is most experience at a time of maximum migration to the Mediterranean islands and to Italy from Somalia, Sudan, Cote d'Ivoire, Tunisia, and Libya. Members attended the workshop hosted by Aldo Morrone at the San Gallicano Hospital, Rome, Italy. Issues discussed were the size of the problem, ethics and legality, potential value of the migrant, dermatologist as carer, challenges met by interpretation, good listening, and transcultural mediation. The experiences of the National Institute for Health Migration and Poverty at the San Gallicano Hospital in Rome, Ethiopia, Malta, and Lampedusa were key to the development of guidelines on cultural competence.